Persepsi Pelajar Terhadap Pengajaran dan Pembelajaran - Elias, Habibah; Lope Pihie, Zaidatol Akmaliah; Mahyuddin, Rahil (Penerbit Universiti Sains Malaysia, 1995)
This paper discusses the findings of a study which examined trainee teachers' perceptions of teaching and learning. The sample comprised 162 student-teachers undergoing various academic programmes in a Malaysian university. The results showed that teaching was perceived as either a 'directed' or an 'open' activity. Seventy-two percent of the students perceived teaching as a 'directed' activity in which teaching was structured and teacher-centred. This category of students also saw the teachers as the main source of knowledge.